(untitled) (Research, Society and Development, 2021)
Anthropometry and body composition evaluation in boys with Duchenne muscular dystrophy (DMD) are challenging, but crucial methods to evaluate the nutritional status, and better anthropometric reference values and body composition predictive equations are needed for this population. Based on these aspects, this study aimed to investigate the hypothesis that changes in anthropometric parameters and body composition of boys with DMD occur according to age. A cross-sectional study with 49 individuals diagnosed with DMD at the neurological outpatient facility at the Onofre Lopes University Hospital in Natal, Brazil, was performed between September 2016 and March 2019. These individuals underwent anthropometric and body composition evaluation. According to age, the participants were divided into four groups: G1 (2.6 - 8.2y), G2 (8.5 - 10.8y), G3 (11.0 - 14.0y), and G4 (15.9 - 23.0y). The parameters weight-for-age (W/A) (p=0.025), tricipital skinfold (TSF) (p=0.027), adductor pollicis muscle (p=0.041), and corrected arm muscle area (cAMA) (p=0.005) were different among the groups. Regarding anthropometric parameters, was prevalence in the categories of appropriate W/A and a height-for-age (H/A), and eutrophy for body mass index-for-age (BMI/A). For the TSF, there was a higher frequency of severe malnutrition or obesity. The cAMA indicated severe malnutrition in most individuals. As for %FM, high adiposity was more frequent, increasing over age groups (G1 to G4). The boys with DMD presented different patterns of anthropometric and body composition parameters. An increase of fat mass and a decrease of lean mass with age/disease progression were observed.